Model Analisis Sentimen pada Ulasan Pengguna Mobile Banking Menggunakan Kombinasi K-Means dan Naive Bayes - Cahayana, Nika Nur; Aesyi, Ulfi Saidata; Kharisma, Kharisma (Institut Teknologi Dirgantara Adisutjipto, 2025)
Application Mobile Banking Sumsel Babel (BSB) faces the problem of low user satisfaction with a System Usability Scale (SUS) score of 31.46, which is included in the